Cytoplasmic Lipases—A Novel Class of Fungal Defense Proteins Against Nematodes - Tayyrov, Annageldi; Wei, Chunyue; Fetz, Céline; Goryachkin, Aleksandr; Schächle, Philipp; Nyström, Laura; Künzler, Markus (Frontiers in Fungal Biology, 2021)
Fungi are an attractive food source for predators such as fungivorous nematodes. Several fungal defense proteins and their protective mechanisms against nematodes have been described. Many of these proteins are lectins which are stored in the cytoplasm of the fungal cells and bind to specific glycan epitopes in the digestive tract of the nematode upon ingestion. Here, we studied two novel nematotoxic proteins with lipase domains from the model mushroom Coprinopsis cinerea. These cytoplasmically localized proteins were found to be induced in the vegetative mycelium of C. cinerea upon challenge with fungivorous nematode Aphelenchus avenae. The proteins showed nematotoxicity when heterologously expressed in E. coli and fed to several bacterivorous nematodes. Site-specific mutagenesis of predicted catalytic residues eliminated the in-vitro lipase activity of the proteins and significantly reduced their nematotoxicity, indicating the importance of the lipase activity for the nematotoxicity of these proteins. Our results suggest that cytoplasmic lipases constitute a novel class of fungal defense proteins against predatory nematodes. These findings improve our understanding of fungal defense mechanisms against predators and may find applications in the control of parasitic nematodes in agriculture and medicine.